Choosing the Joneses : Endogenous Goals and Reference Standards - Markus Knell; Armin Falk (Institute for the Study of Labor (IZA), 2004)
A growing economic literature stresses the importance of relative comparisons, e.g., for savings and consumption or happiness. In this literature it is usually assumed that reference standards against which people compare themselves are exogenously given. In contrast findings from social psychology suggest that people play an active role in determining their reference standards. We present a social comparison model where people choose their reference standards to serve motives of self-improvement and self-enhancement. The model predicts that reference standards increase in individuals? abilities and that thus people tend to compare themselves to similar others. The results of a questionnaire study confirm the model?s prediction.
Keywords: Z13; D62; D63; H31; 330; reference standard; goals; social comparison; happiness; Lebensqualität; Konsumentenverhalten; Konsuminterdependenz; Soziale Beziehungen; Entscheidung; Experiment; Schweiz